Pharmacological Modulation of Sleep Homeostasis in Rat: Novel Effects of an mGluR2/3 Antagonist - Hanley, Nicola; Paulissen, Jerome; Eastwood, Brian J; Gilmour, Gary; Loomis, Sally; Wafford, Keith A; McCarthy, Andrew (Sleep (New York, N.Y.), 2019)
Increasing vigilance without incurring the negative consequences of extended wakefulness such as daytime sleepiness and cognitive impairment is a major challenge in treating many sleep disorders. The present work compares two closely related mGluR2/3 antagonists LY3020371 and LY341495 with two well-known wake-promoting compounds caffeine and d-amphetamine. Sleep homeostasis properties were explored in male Wistar rats by manipulating levels of wakefulness via (1) physiological sleep restriction (SR), (2) pharmacological action, or (3) a combination of these. A two-phase nonlinear mixed-effects model combining a quadratic and exponential function at an empirically estimated join point allowed the quantification of wake-promoting properties and any subsequent sleep rebound. A simple response latency task (SRLT) following SR assessed functional capacity of sleep-restricted animals treated with our test compounds. Caffeine and d-amphetamine increased wakefulness with a subsequent full recovery of non-rapid eye movement (NREM) and rapid eye movement (REM) sleep and were unable to fully reverse SR-induced impairments in SRLT. In contrast, LY3020371 increased wakefulness with no subsequent elevation of NREM sleep, delta power, delta energy, or sleep bout length and count, yet REM sleep recovered above baseline levels. Prior sleep pressure obtained using an SR protocol had no impact on the wake-promoting effect of LY3020371 and NREM sleep rebound remained blocked. Furthermore, LY341495 increased functional capacity across SRLT measures following SR. These results establish the critical role of glutamate in sleep homeostasis and support the existence of independent mechanisms for NREM and REM sleep homeostasis.